Parents knowledge and attitude on childhood immunization in a tertiary care teaching hospital (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Aim: The main aim of this study was to assess the Knowledge and attitudes of mothers with children less than twelve years of age about vaccination.Materials &Methods: A prospective observational study was conducted for a period of six months in a tertiary care teaching hospital.  A multi optional questionnaire was used. Descriptive statistics were used to describe all variables. Association between dependent variables and independent ones were tested using Chi-square test. P values of < 0.05 were considered statistically significant.Results: In the present study almost 64% of the parents replied that they knew about childhood immunization. We have assessed that there was no significant difference between the genders. When the socio demography was assessed, a low literacy level was found in the rural mothers and p value is (0.00001).This was significant and needs to be addressed in order improve knowledge about vaccinations. Our study has found a significant difference in parents from urban and rural areas in terms of their knowledge and attitude regarding vaccination. There is no significance difference between knowledge and attitude of parents who already had children and number of children.Conclusion: The present research showed that parents had good knowledge and positive attitudes related to immunization. Majority of the parents in rural areas were unaware about the vaccination and its implications when compared with the parents in urban areas. Educational interventions are needed to upgrade parents knowledge with special emphasis on less educated and residents of rural areas.